Quality Management Development of Boarding School Education in West Java: Research at Mifathul Huda Manonjaya Islamic Boarding School Tasikmalaya, Suryalaya Islamic Boarding School and Al-Ittifaq Ciwidey Islamic Boarding School - Yusup Ridwan; Nina Nurmila; Mohamad Erihadiana; Asep Nursobah (Ridwan Institute, 2022)
This study aims to acknowledge the growth of quality management of Islamic boarding school education in the input, process, output, and results of students toward the quality management of pesantren education. The research method used is a qualitative approach and a case study method with data collection techniques through in-depth interviews, field observations and documentation studies. The results of the study are (1) quality planning for Islamic boarding schools is based on the development of educational strategies (education development strategies) and total quality management (TQM) in quality management. Mitahul Huda Manonjaya Islamic Boarding School Tasikmalaya with its salafiyah system based on the mu'adah curriculum, Suryalaya Islamic Boarding School with its hifdutthariqoh development (Tareqat Qadiriyah Naqsyabandiyah) and Al-Ittifaq Islamic Boarding School with its agribusiness development, (2) implementation of the quality of education through the development of institutional quality management based on the leadership of Kyai who have the spirit of taffaquh fi addin, human resources by maximizing the productivity of the management of experts, competent and highly dedicated to Islamic boarding schools, (3) evaluation of education quality management in the three Islamic boarding schools is carried out systematically, effectively and efficiently by developing a follow-up plan (RTL) along with its achievement indicators, (4) education quality management problems faced by the three Islamic boarding schools are not yet evenly distributed in the competence and qualifications of educators and education, limited infrastructure, supervision systems and technology, and (5) efforts to improve education quality management in the three Islamic boarding schools by developing competitive and competitive quality management the potential resources of each Islamic boarding school.